The Prime Enforcement of Tax Amnesty Regulation in Indonesia: Evidence from Tax Aggressive Firms - Yani Permatasari; Agnes Aurora Ngelo; iman Harymawan; Suham Cahyono (Universitas Muhammadiyah Malang, 2023)
Purpose: This study examines the response of tax aggressive companies to the prime enforcement of the tax amnesty in Indonesia. Specifically, this study examines their tax aggressive behavior in the period and post-period of tax amnesty. Methodology/approach: The author(s) use all Indonesian companies in 2010-2018 listed in the IDX and analyze using logit and OLS regression analysis techniques. Findings: The results suggest that companies that had been tax aggressive in the pre-period of a tax amnesty program are more likely to participate in Indonesia's prime tax amnesty program. Furthermore, we discover that those tax aggressive companies had become less aggressive in the period and post-period of tax amnesty. These findings are robust to several proxies of tax aggressiveness and Coarsened Exact Matching (CEM) method to handle potential endogeneity problems. We employ Indonesia's unique setting, one of a few developing countries that implement the tax amnesty successfully for the first time. Practical implications: These findings are expected to provide evidence of the effectiveness of the tax amnesty implementation in Indonesia. The results could give insight for policymakers to thoroughly consider the costs and benefits of tax amnesty, and if there is a repeated implementation. Originality/value: This study did not include any further test of the corporate governance mechanism involved in the relationship between tax aggressive companies and tax amnesty participation. Therefore, future studies could consider the limitations and address the issue.